Genetically predicted tea intake increases the risk of osteoarthritis: A Mendelian randomization study - Li, Gang; Zhang, Zhe; Liu, Yang (Frontiers in Genetics, 2022)
Background: The purpose of this study was to clarify the relationship between tea consumption and osteoarthritis (OA). Methods: Our analysis of the common single-nucleotide polymorphisms (SNPs) from the Open Genome-wide Association Studies database was based on the data collected. In addition, summary statistics regarding OA were retrieved from the second dataset enrolling 50508 participants (10083 OA cases) of European ancestry. The causal association between tea intake and OA was tested using two-sample Mendelian randomization analyses (MR). Results: Tea consumption has adverse effects on OA. (inverse-variance weighted method: OR=1.19, 95% CI=1.08–1.30; weighted median method: OR=1.22, 95% CI=1.07–1.40). There was no evidence of directional pleiotropy in the MR–Egger regression intercept (MR intercept=−0.002; P=0.770), and no evidence of underlying heterogeneity in MR analysis according to Cochran's Q test and funnel forest analysis. Conclusion: A genetically predicted higher daily tea intake increases the risk of OA.